The complete chloroplast genome sequence of Lepidium perfoliatum L. - Qian Zhou; Wei-Jun Zeng; Ji-Lian Wang; Yu-Zhou Wang; Yun Chen; Kaidiriye Yusupul; Hui-Xin Zhao (Mitochondrial DNA. Part B. Resources, 2021)
This study was based on the collection of the complete genome of Lepidium perfoliatum chloroplast (cp). The full cp genome is 154,264 bp long, containing 130 genes, in which 8 genes are specified for ribosomal RNA (rRNA), while 85 and 37 genes for protein-coding and transfer RNA (tRNA) respectively. Phylogenetic analyss revealed the closed cluster of Lepidium perfoliatum with other Lepidium species such as Lepidium apetalum, Lepidium sativum, Lepidium meyenii and Lepidium virginicum, which helps for the evaluation of how Lepidium perfoliatum is phylogenetically related to other species.